Effectiveness of interventions that support penicillin allergy assessment and de-labeling of patients by non-allergy specialists: a systematic review protocol - Powell, N; Kohl, D; Ahmed, S; Kent, B; Sandoe, J; Tonkin-Crine, S; Owens, R; Stephens, J; Upton, M (Lippincott, Williams & Wilkins, 2021)
Objective: This review will systematically examine and synthesize the evidence evaluating the effectiveness and safety of interventions that enable non-allergy specialist health care workers to assess allergy risk in patients with reported penicillin allergies and subsequently remove erroneous allergy records.